Adult sex-ratio in ostracods and its implications for sexual selection. Issue 3 (3rd July 2019) - Fernandes Martins, Maria João
ABSTRACT: The Ostracoda – ubiquitous aquatic micro-crustaceans – show an exceptionally high incidence of female-biased adult sex ratio. Intraspecific sex ratio is known to vary in extant species and yet in the fossil record a species' adult sex ratio can be highly stable across time. Sex ratio conditions the intensity of sexual selection and influences which sex undergoes stronger selective pressure. However, the impact of variation in spatial and temporal intraspecific sex ratio on the evolution of sexual selection remains an open question, calling for further investigations on the factors controlling adaptive sex ratio. This mini-review aims to introduce the system, and explores some of the key literature addressing factors influencing intraspecific variation in adult sex ratio (ASR) and its implication in the intensity of sexual selection and evolution of mating systems.